Savings and Loans Program, The Revenue of Small Micro Enterprises and Poverty Reduction among Women Groups - Ana Zahrotun Nihayah (Shirkah: Journal of Economics and Business, 2017)
This research aims to understand the micro small medium business income both before and after receiving the program, to find out the number of poverty reduction, and to see the application of Islamic economic values on the women’s saving and loans program.The population of this research are members of the women’s saving and loans program, which is 215 people in total and scattered in 16 business group. Using random sampling techniques, there are 70 people that was taken into consideration. The method analysis used in in this research is using Wilcoxon rank test analysis, the poverty reduction analysis, and the Islamic economics values. Based on data analysis is(1) founded that the women’s saving and loans program affecting the micro small medium enterprises income. (2) Due to the women’s saving and loans program there are decreasing number of poverty rate about 20 percent. (3) It is realized that there are some applications of Islamic economics values upon the women’s saving and loans program, they are time extensions, fine replacement, social activities, and the improvement of society welfare.Keyword: micro small medium business, islamic economic values, saving and loans program